Clinical efficacy of membrane-free stem cell extracts for the treatment of canine atopic dermatitis - Kim YS; Ha SE; H Bae; D Lee; Yu DH; Kim GS (Veterinární Medicína, 2022)
Despite various treatment options for canine atopic dermatitis (cAD), therapeutic limitations still exist, including adverse effects and low absorption ratios. This study evaluated the effects of a membrane-free stem cell extract (MFSCE) on the clinical signs of atopic dogs. Thirty client-owned dogs previously diagnosed with cAD were separated into placebo (n = 10) and MFSCE-treated groups (n = 20). The dogs were treated with a cream (MFSCE and placebo) via dermal administration twice daily for 14 days, and the clinical response was recorded on days 0, 7, and 14. The MFSCE-treated group showed significantly decreased severity of pruritus on day 14 compared to that on day 0. In addition, the erythema, pigmentation, skin dryness, and thickness were remarkably decreased in the MFSCE-treated group on day 14 compared to those on day 0 whereas no significant changes were observed in the placebo-treated group. No general clinical signs or adverse effects were observed in this study. These results suggest that MFSCE could be a surrogate treatment option for cAD.